1994
DOI: 10.1111/j.1365-2249.1994.tb06127.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the virulence of Mycobacterium avium complex (MAC) isolates in mice

Abstract: SUMMARYThe virulence of different isolates of MAC was studied in naturally susceptible BALB/c mice. In preliminary experiments, MAC bacteria forming smooth transparent colonies on solid media (SmT variants) were found to be virulent for BALB/c mice, causing progressive infection; smooth opaque (SmOp) were generally avirulent, being slowly eliminated from the infeeted organs; and rough (Rg) variants were either avirulent or as virulent as SmT variants. We chose to compare the virulence of different isolates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 21 publications
2
34
0
1
Order By: Relevance
“…Furthermore, it was found that most bird isolates had similar IS901 patterns. These isolates were also shown to be strikingly more virulent than AIDS patient isolates in BALB/c mice (142,204). Evidence that a more pathogenic subset of M. avium exists has been advanced numerous times since, leading some to simply divide M. avium isolates into those that are IS901 ϩ and those that are IS901 Ϫ (68).…”
Section: Genetic Methods To Detect Is Elementsmentioning
confidence: 99%
“…Furthermore, it was found that most bird isolates had similar IS901 patterns. These isolates were also shown to be strikingly more virulent than AIDS patient isolates in BALB/c mice (142,204). Evidence that a more pathogenic subset of M. avium exists has been advanced numerous times since, leading some to simply divide M. avium isolates into those that are IS901 ϩ and those that are IS901 Ϫ (68).…”
Section: Genetic Methods To Detect Is Elementsmentioning
confidence: 99%
“…Mice were infected with M. avium strain 724, which has been characterized previously (31) and was a kind gift from T. Ulrichs, Max Planck Institute for Infectious Biology, Berlin, Germany. Following 3 weeks of growth in Dubos broth at 37°C, mycobacteria were suspended in sterile saline containing 0.05% Tween 20 and kept at Ϫ80°C until they were used.…”
Section: Animalsmentioning
confidence: 99%
“…MAC is not pathogenic for guinea pigs and rats . Pedrosa et al (1994) described the investigation focused on the virulence of various MAC isolates in naturally susceptible BALB/c mice. Gross lesions that develop after the infection with MAC members differ from lesions caused by the MTC members in the majority of animal species.…”
Section: Avium Complex Membersmentioning
confidence: 99%